2013 RoEduNet International Conference 12th Edition: Networking in Education and Research 2013
DOI: 10.1109/roedunet.2013.6714191
|View full text |Cite
|
Sign up to set email alerts
|

Open cloud platform for programming embedded systems

Abstract: Wyliodrin is an open cloud platform for embedded systems that allows users to control and monitor their boards in real time at distance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Supplementary Figure 3 represents device management screen where device configuration can be edited for device type, brand name and device name on the same Beaglebone MAC id so that if the medical device is upgraded for a newer version or completely changed, it could be remotely managed. Currently, industry grade remote monitoring solutions for embedded devices [41]- [44] are not available for BBB on ARM technology. Hence we provisioned vital tracker and heartbeat screen to closely monitor any data loss.…”
Section: Technicalmentioning
confidence: 99%
“…Supplementary Figure 3 represents device management screen where device configuration can be edited for device type, brand name and device name on the same Beaglebone MAC id so that if the medical device is upgraded for a newer version or completely changed, it could be remotely managed. Currently, industry grade remote monitoring solutions for embedded devices [41]- [44] are not available for BBB on ARM technology. Hence we provisioned vital tracker and heartbeat screen to closely monitor any data loss.…”
Section: Technicalmentioning
confidence: 99%
“…The other components that are part of this stage are three resistors (R8 ÷ R10). The signal at the output of the level shifting stage is defined by: (2) In equation (2) with ADC_INPUT is denoted the output signal of the stage presented in this subsubsection (which will be connected to the input of the ADC) and with AMP_OUT is denoted the signal at the output of the programmable gain amplifier, in order to easily identify them on the schematic diagram presented in figure 2. It can be observed that this stage amplifies the input signal with a gain equal to 1.5 and then adds a constant voltage equal to 2.5 V to it.…”
Section: The Level Shifting Stagementioning
confidence: 99%
“…Since the Internet of Things (IoT) idea, almost every device is designed in such way that it can be connected to the Internet [1], becoming accessible and controllable from anywhere. Another word that characterizes the near future is "open" as more and more open source software [2]. Also raw hardware resources (electronic components) become available to anyone interested since their prices keep dropping.…”
Section: Introductionmentioning
confidence: 99%